AppEduTV3.0: Aplicativo Educacional para a TV 3.0: Possibilidades e desafios para um aplicativo educacional considerando o estado da arte da TV 3.0 - Barrére, Eduardo; Sousa, Li-Chang Shuen; Muchaluat-Saade, Débora C.; Moreno, Marcelo Fereira; Soares Neto, Carlos de Salles; Santos, Joel A. F. dos; Josué, Marina Ivanov; Vieira, Rômulo; Costa, Iago Victor Silva; Gonçalves, João Víctor Cruz; Sousa, Sarah Regina Bezerra (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2025)
This paper presents the development of the AppEduTV3.0 project, which sought to explore the potential and limitations for the development and use of educational applications in the context of TV 3.0. AppEduTV3.0 proposes an ecosystem for the development of these applications by public television broadcasters, based on filling out templates that generate the application for a specific television program. The app can be run in three different scenarios: a single user with internet access; a single user without internet access; and a classroom with internet access. The prototype created as proof of concept allowed, among other things, to identify limitations due to the absence of standardization.